Pendidikan Berbasis Islamic Worldview: Membangun Karakter dan Moral Bangsa - Khotimah, Anisa Nur; Mujahid, Kasori (Lembaga Yasin AlSys, 2025)
Islamic worldview-based education is an educational approach that is based on Islamic values ​​and views the world from an Islamic perspective. Educators play a very important role in implementing Islamic worldview-based education to shape the character and morals of the nation. The role of educators includes integrating Islamic values ​​into the curriculum, shaping students' character, developing critical thinking skills, communicating effectively, working together, and making decisions. Thus, educators can help students become individuals who are moral, have integrity, and have the ability to face challenges and difficulties in everyday life. This study aims to examine the role of educators in implementing Islamic worldview-based education and shaping the character and morals of the nation.